Serum High Mobility Group Box 1 (HMGB1) Protein Levels and Cognitive Function in Epilepsy Patients: A Cross-Sectional Study - Rahmi Ulfa; Syafrita, Yuliarni; Lydia Susanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Epilepsy is a neurological disease with a high incidence rate. Cognitive decline is one of the consequences of recurrent seizures. Neuroinflammation is closely related to the development of epilepsy and cognitive impairment. An increase in the expression and translocation of High Mobility Group Box 1 (HMGB1) from the nucleus to the extracellular space has been observed in epilepsy patients and experimental animal models. This study aimed to investigate the relationship between serum HMGB1 levels and cognitive function in epilepsy patients. Methods: This cross-sectional observational study involved 45 epilepsy patients. Cognitive function was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina), and serum HMGB1 levels were measured using the ELISA technique. The relationship between cognitive function and HMGB1 levels was analyzed using the Kruskal-Wallis test, with a significance level set at p < 0.05. Results: The mean age of the participants was 28.5 years, with a higher proportion of females. The mean serum HMGB1 level was 22.6 ng/ml. No significant relationship was found between serum HMGB1 levels and cognitive function in epilepsy patients (p = 0.188). Conclusion: Serum HMGB1 protein levels were not associated with cognitive function in this sample of epilepsy patients.